Pengaruh Video Tutorial Penggunaan Software Mastercam terhadap Minat Belajar Siswa pada Mata Pelajaran NC/CNC dan CAM di SMK Negeri 1 Padang - Hidayat, Rohman; Purwantono, Purwantono; Prasetya, Febri; Kurniawan, Andre (Lembaga Yasin AlSys, 2024)
This research aims at the following two things. First, to find out how the level of interest in learning class XII students at SMK Negeri 1 Padang after being given the treatment of video tutorial-based learning media. Second, to determine whether or not there is an influence given before and after being given the treatment of video tutorial-based learning media, besides that it also sees how much influence is obtained. This study uses a quantitative type approach and with a quasi experimental method and this research design uses One group pretest-posttest design. Based on the results of research conducted related to the effect of video tutorial-based learning media on student learning interest, the following 3 conclusions can be drawn. First, the pretest value is included in the good category while the posttest value is included in the very good category when viewed based on the reference category of pretest and posttest learning interest. Second, the provision of learning media can have a significant effect on increasing the value of students' interest in learning because of an increase. Third, there is an influence given based on the results of the t-test hypothesis which states Ho is rejected and Ha is accepted. This indicates that there is a significant influence between the provision of tutorial video-based learning media on student interest in learning.